2011
DOI: 10.1186/1475-2840-10-100
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance increases the occurrence of new cardiovascular events in patients with manifest arterial disease without known diabetes. The SMART study

Abstract: BackgroundInsulin resistance is accompanied by a cluster of metabolic changes, often referred to as metabolic syndrome. Metabolic syndrome is associated with an increased cardiovascular risk in patients with manifest arterial disease. We investigated whether insulin resistance is associated with an increased risk for cardiovascular events in patients with manifest arterial disease without known diabetes and whether this can be explained by the components of the metabolic syndrome or by inflammation.MethodsPros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…[29,30], insulin resistance [7,31], diabetes mellitus [8,11], increased oxidative stress [32,33], inflammatory reactions [34,35] as well as mutations on genetic levels [36][37][38], of which the risks rise proportionally associated with MSC.…”
Section: Resultsmentioning
confidence: 99%
“…[29,30], insulin resistance [7,31], diabetes mellitus [8,11], increased oxidative stress [32,33], inflammatory reactions [34,35] as well as mutations on genetic levels [36][37][38], of which the risks rise proportionally associated with MSC.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that insulin resistance and metabolic syndrome increase the risk of new cardiovascular events also in patients without known diabetes but with manifest arterial disease [26]. In type 2 diabetes, metabolic syndrome is highly prevalent and often precedes hyperglycaemia onset [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…This high cardiovascular risk may be due to a combination of non-classical risk factors associated with insulin resistance, e.g. inflammation, hyperinsulinemia, oxidative stress, and hypercoagulability, together with the separate components of metabolic syndrome [28,29]. …”
Section: Discussionmentioning
confidence: 99%